PENYULUHAN DAN PERBANYAKAN MUSUH ALAMI SEMUT HITAM ( DOLICHEDERUS THORACICUS ) UNTUK MENGENDALIKAN HAMA HELOPELTIS, SP PADA KAKAO KABUPATEN SIKKA - Vincensia Alvina Mita; Yovita Yasintha Bolly; Mario Malado (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2025)
This extension and training activity aimed to improve farmers’ knowledge and skills in propagating the black ant (Dolichoderus thoracicus) as a natural enemy for the biological control of Helopeltis . on cocoa plants. The activity methods included field observation, collection of black ant colonies, construction of artificial nests, maintenance, and monitoring of colony development. Colony propagation was conducted using two types of artificial nests: plastic nests filled with dried cocoa leaves supplemented with sugar solution and shrimp paste, and coconut leaf sheath nests treated with sugar solution and shrimp paste bait. The results showed that black ants play an effective role as biological control agents. The presence of ant colonies around cocoa plants reduced Helopeltis populations through aggressive behavior that repelled and attacked the pests. Prior to propagation, the number and distribution of ant colonies were limited, resulting in suboptimal pest control. After colony propagation and relocation, the number and distribution of ant colonies increased and became more uniform. Plastic nests containing dried cocoa leaves were more rapidly colonized and supported stable colony growth. The use of black ants as biological control agents is environmentally friendly, low-cost, and easy to apply by cocoa farmers, reducing dependence on chemical pesticides.